2009
DOI: 10.1017/s1751731109990395
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of live animal muscular and skeletal scores, ultrasound measurements and carcass classification scores with carcass composition and value in steers

Abstract: This study examined the relationship of muscular and skeletal scores and ultrasound measurements in the live animal, and carcass conformation and fat scores with carcass composition and value using 336 steers, slaughtered at 2 years of age. Live animal scores and measurements were recorded at 8 to 12 months of age and pre-slaughter. Following slaughter, each carcass was classified for conformation and fatness and the right side dissected into meat, fat and bone. Carcass conformation scores and fat scores were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
(41 reference statements)
2
19
0
1
Order By: Relevance
“…Previous studies using 336 steers (Conroy et al, 2009a) and 74 bulls (Conroy et al, 2009b) showed carcass conformation and fat scores to be potential predictors of carcass meat, fat and bone proportions. This study includes animals used by Conroy et al (2009a and2009b) in addition to bulls, heifers Table 4 Prediction equations for meat, fat and bone proportion estimated using a linear model on the entire data set (662 animals) using hindquarter weights. The table contains the intercept and regression coefficient of the regression model estimated from the entire data set including the R 2 of the model fit using the entire data set.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies using 336 steers (Conroy et al, 2009a) and 74 bulls (Conroy et al, 2009b) showed carcass conformation and fat scores to be potential predictors of carcass meat, fat and bone proportions. This study includes animals used by Conroy et al (2009a and2009b) in addition to bulls, heifers Table 4 Prediction equations for meat, fat and bone proportion estimated using a linear model on the entire data set (662 animals) using hindquarter weights. The table contains the intercept and regression coefficient of the regression model estimated from the entire data set including the R 2 of the model fit using the entire data set.…”
Section: Discussionmentioning
confidence: 99%
“…Following a period of 24 h at 48C, the right side of each carcass was quartered at the fifth rib into an eight-rib hindquarter (pistola) and the remaining forequarter. After recording the weight, the hindquarter was dissected into 13 cuts (leg, heel, silverside, topside, knuckle, rump, tail of rump, cap of rump, fillet, strip loin, cube roll, cap of rib and eye of the round) from which all visible fat and bone (where applicable) were removed (Conroy et al, 2009a). The weight of each individual meat cut and total fat from the hindquarter was recorded, as was bone weight following the removal of all adhering lean tissues.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations